Internalization of Sharia Muamalah Values to Improve Islamic Economic Literacy among High School Students - Muhammad Syaipudin; Mifta Hasda; Saru Reza (Journal of Community Service and Empowerment, 2026)
The rapid development of the digital economy has increased young people's involvement in various economic activities. However, this development has not been fully accompanied by adequate understanding of Islamic economic values. The low level of Islamic financial and economic literacy may lead students to make economic decisions without considering ethical aspects and Islamic principles. This community service program aimed to improve students’ understanding of Islamic economic values and encourage the development of economic behavior that aligns with Sharia principles. The program was conducted at SMA IT Al Utsaimin Bangkinang and involved 48 tenth-grade students. The methods employed included presentations, discussions, question-and-answer sessions, and case-based learning related to students’ daily experiences. The materials covered Islamic economic values, lawful wealth acquisition, consumption and distribution according to Sharia principles, Islamic financial planning, the implementation of Islamic economics in daily life, and the development of Islamic banking in Indonesia. The results indicated that participants actively engaged in the program and gained a better understanding of Islamic economic principles, particularly regarding electronic money, digital transactions, and personal financial management. The activity also enhanced students’ awareness of the importance of honesty, fairness, transparency, and responsibility in economic activities. Therefore, this community service program contributed to strengthening Islamic economic literacy and supporting the development of a young generation that is knowledgeable, ethical, and responsible in responding to the challenges of the modern economy.